Using Actor Network Theory (ANT) as an analytic tool in order to effect superior PACS implementation. (20th September 2007) - Wickramasinghe, Nilmini; Tumu, Srinnath; Bali, Rajeev K.; Tatnall, Arthur
Currently, one of the major challenges facing healthcare organisations globally is to judiciously apply new technologies and intelligently re-design antiquated processes and structures so that the application of these new technologies will be optimal. In so doing, it is believed that healthcare organisations will then be better positioned to offer cost effective, quality healthcare delivery. However, this is not a simple task since it is often difficult to articulate and quantify the benefits of such technologies, while the costs to implement them represent a significant financial drain. One such technology that healthcare organisations currently struggle to cost justify and successfully implement is Picture Archiving Communication System (PACS). In this paper we submit that, by using Actor Network Theory (ANT) as an analysis tool, it is possible to effect superior PACS implementations.